1993
DOI: 10.1099/0022-1317-74-10-2061
|View full text |Cite
|
Sign up to set email alerts
|

Mouse hepatitis virus spike and nucleocapsid proteins expressed by adenovirus vectors protect mice against a lethal infection

Abstract: Infection with the mouse hepatitis coronavirus (MHV) provides an excellent model for the study of viral diseases of the central nervous system and the gastrointestinal tract. With the ultimate aim of studying mucosal immunity to MHV we have cloned the genes encoding the structural proteins of MHV strain A59 (MHV-A59) into the E3 region of a human adenovirus type 5 vector. Infection of HeLa cells with the resulting recombinant adenoviruses AdMHVS, AdMHVN and AdMHVM revealed the correct expression of the spike (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…In the case of murine hepatitis virus, its immunodominant sites responsible for eliciting protective humoral responses are mainly located in the S protein S1 domain (21,22). The S protein of transmissible gastroenteritis virus contains four major antigenic sites (A to D), and site A on the S1 subunit is the main inducer of neutralizing Abs (23)(24)(25).…”
Section: S Evere Acute Respiratory Syndrome (Sars)mentioning
confidence: 99%
“…In the case of murine hepatitis virus, its immunodominant sites responsible for eliciting protective humoral responses are mainly located in the S protein S1 domain (21,22). The S protein of transmissible gastroenteritis virus contains four major antigenic sites (A to D), and site A on the S1 subunit is the main inducer of neutralizing Abs (23)(24)(25).…”
Section: S Evere Acute Respiratory Syndrome (Sars)mentioning
confidence: 99%
“…Studies from other animal CoV vaccines have shown that the CoV nucleocapsid (N) protein may represent another antigen candidate for vaccine development (Anton et al, 1996;Olsen, 1993). Although antibodies to CoV N proteins have no virus-neutralizing activity, there is evidence that the protein may provide protection in vivo by induction of cell-mediated immunity, although it has also been suggested to induce eosinophilic infiltrates resulting in immunopathology (Deming et al, 2006;Enjuanes et al, 1995;Stohlman et al, 1995;Wesseling et al, 1993). N protein has been shown to generate CoV-specific CD8 + T cells (Boots et al, 1991;Seo et al, 1997;Stohlman et al, 1993Stohlman et al, , 1995; it also provides protection in animals in response to infection by animal CoV (Collisson et al, 2000;Seo et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…A live recombinant Ad5 vector has been demonstrated to be an effective rabies vaccine when administered to skunks and foxes by the oral route (Charlton et al, 1992). Ad5 has been used successfully for expression of the S protein of the coronavirus mouse hepatitis virus (Wesseling et al, 1993).…”
mentioning
confidence: 99%